A scientific-technical basis for an Agroclimatic Law in Argentina - Victoria, María Adriana (Przegląd Prawa Rolnego, 2019)
There is a bidirectional relationship between the transverse and transdisciplinary phenomenon and the agricultural activity (technical fact) as they affect each other. Scientific, technical and technological knowledge constitute the basis of international public climate law that is made effective through national climate law, and can be conformed to a national agroclimatic law, authentic “ius novum,” “in fieri,” with specific norms of incidence in the agroclimate, referred to as: environment, renewable natural resources, natural phenomena and the agrarian activity of ecological substrate and regulated technical component. The implementation of international solutions could contribute to the sustainable development of the rural world and the resilience of agroecosystems and is recommended be adopted in the law on agroclimatic change proposed for Argentina.